The Socialist Commitment in Karl Barth - Ward, W. Reginald (Studies in church history, 1978)
The young Karl Barth is not an easy man to assess. It is not just that he covered a major theological revulsion by violent polemics, nor even that in the second world war he became a cult figure with hard-pressed protestants everywhere, overwhelmed by the need to save their churches from the destructive compromises of the church leaders, and subsequently, more briefly, a cult figure with a new theological establishment. More recently the young Karl Barth has been the victim of disputes over the uses to which Barthianism can be put. In the German student revolt the need to unify thought and action in politics and theology exposed a generation gap; a burning concern to many theological students, it embarrassed many of their teachers. At the Kirchliche Hochschule in Berlin, a bastion of Barthianism, Friedrich-Wilhelm Marquardt, a pupil of Hellmut Gollwitzer, sought to bridge the gap by showing that from beginning to end the core of Barth’s theology was a socialist commitment. (The first paragraph of this book reads starkly, ‘Karl Barth was Socialist’.) The perspective first opened by the student movement was confirmed by Marquardt’s editorial work on Barth’s Safenwil remains, and especially on forty three socialist speeches. Marquardt worked out his view systematically in a Habilitationschrift which was rejected at the Kirchliche Hochschule as unwissenschaftlich. Gollwitzer made a public scene, got the book published, and took the whole argument further in a long essay of his own. The clinching evidence (if diat is what it really is) of the speeches is under the terms on which Karl Barth’s unpublished remains are being edited until the volume in which they are to be incorporated is published. Yet most of the voluminous material ever likely to be available for the young Barth is now in print, and it is worth examining in its own right, as distinct from being expounded in the light of the Church Dogmatics with Marquardt.